Bcl-2 confers survival in cisplatin treated cervical cancer cells: circumventing cisplatin dose-dependent toxicity and resistance. Issue 1 (December 2015) - Leisching, Gina; Loos, Benjamin; Botha, Matthys; Engelbrecht, Anna-Mart
Abstract Background Cisplatin is the main chemotherapeutic drug for the treatment of cervical cancers, however resistance to cisplatin is increasingly common and therefore has limited the efficacy and use of this drug in the clinic. Dose-dependent toxicity poses an additional challenge since patients suffer long-term and often permanent side-effects after treatment. Bcl-2 up-regulation has been implicated in the resistance to cisplatin in a variety of cancer cell lines, however its role in cervical cancer is confounding. Methods A low, non-cytotoxic concentration of cisplatin was used in the treatment of HeLa and CaSki cells. Bcl-2 expression was determined through Western blotting and immunocytochemistry before and after treatment with cisplatin. To assess the reliance of the cervical cancer cells on Bcl-2 in the presence of cisplatin, Bcl-2 knock-down was achieved through RNA interference, where after apoptosis was assessed through PARP cleavage (Western blotting), Caspase activity (Caspase-Glo© ) and PI inclusion analysis (Flow cytometry). Finally, pre-malignant and malignant cervical tissue was analysed for the presence of Bcl-2 through Western blotting and immunofluorescence. Results Cervical cancer cells upregulate Bcl-2 when treated with a non-cytotoxic concentration of cisplatin, which when silenced, effectively enhanced cisplatin sensitivity, and therefore significantly induced apoptosis. Analysis of the expression profile of Bcl-2 in cervical tissue revealed its up-regulation in cervical carcinoma, which agrees with results obtained from the in vitro data. Conclusions Our data strongly suggest that utilising a lower dose of cisplatin is feasible when combined with Bcl-2 silencing as an adjuvant treatment, thereby improving both the dose-dependent toxicity, as well as cervical cancer resistance.